Nadi Pariksha (Pulse Diagnosis) - A Traditional Diagnostic Approaches as per Ayurveda - Guguloth, Ramesh; C. R., Yadav; Vasam, Dr. Kashaiah (International Journal of Innovative Research in Medical Science, 2017)
In Ayurveda we find the mention of a very important diagnostic tool referred to as the Ashtvidhpariksha. Nadi pariksha forms an inevitable part of this Ashtvidha Pariksha. Through Nadi we can determine the Prakruti-Vikruti, the status of Doshas in each organ and effects on Dhatus, Manas and Sukshma Sharira. Vata-Pitta-Kapha which forms the base of diagnosis and treatment in Ayurveda; their effect and their current status in the body can be determined only through Nadi Pariksha. Also Bhutpreta Badha mentioned in Ayurveda can also be known through Nadi Pariksha. The information about Nadi is available in the form of Shlokas in our ancient books. The information in the Shlokas is not very clearly written and is mentioned in a very decorative language. Thus, it can be understood only with the proper guidance of a guru. There is evidently no reference about Nadi vijnana in our ancient books like Brihatrayi. Sharangdhara Samhita of 13th century was the first such book which establishes the authentication of Nadi Pariksha. Then in 16th century ‘Bhavprakasha’ also provides proof of some development in the field of Nadi Vijnana. In Yogratnakara of 17th century, complete details and information about Nadi Pariksha can be found. The purpose of the present study is, to impoverish the cognition, a little attempt is made to put.